Noninvasive positive pressure ventilation in unplanned extubation - KARAKURT, SAİT; ÇELİKEL, TURGAY HÜSEYİN (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2009)
Background:Unplanned extubation is quite common in intensive care unit (ICU) patients receiving mechanical ventilatory support. The present study aimed to investigate the effectiveness of noninvasive positive pressure ventilation (NPPV) in patients with unplanned extubation. Materials and Methods: A total of 15 patients (12 male, age: 57 number 24 years, APACHE II score: 19 number 7) monitored at the medical ICU during the year 2004 who developed unplanned extubation were included in the study. NPPV was tried in all of them following unplanned extubation. Indications for admission to the ICU were as follows: nine patients with pneumonia, three with status epilepticus, one with gastrointestinal bleeding, one with cardiogenic pulmonary edema and one with diffuse alveolar bleeding. Results:Eleven of the patients (74) were at the weaning period at the time of unplanned extubation. Among these 11 patients, NPPV was successful in 10 (91) and only one (9) was reintubated due to the failure of NPPV. The remaining four patients (26) had pneumonia and none of them were at the weaning period at the time of extubation, but their requirement for mechanical ventilation was gradually decreasing. Unfortunately, an NPPV attempt for 6-8 h failed and these patients were reintubated. Conclusions:Patients with unplanned extubation before the weaning criteria are met should be intubated immediately. On the other hand, when extubation develops during the weaning period, NPPV may be an alternative. The present study was conducted with a small number of patients, and larger studies on the effectiveness of NPPV in unplanned extubation are warranted for firm conclusions.
Keywords: Intensive care unit; mechanical ventilation; noninvasive positive pressure ventilation; unplanned extubation; NOSOCOMIAL PNEUMONIA; RESPIRATORY-FAILURE; RISK-FACTORS